P449 Selective depletion of LAG3+ cells in T-cell-driven inflammation: a randomised, double-blind, placebo-controlled, FTIH phase I/Ib clinical trial. (25th January 2019) - Ellis, J; Marks, D; Barrett, C; Hopkins, T; Richards, A; Fuhr, R; Albayaty, M; Coenen, M; Liefaard, L; Leavens, K; Nevin, K; Tang, S; et al.
Abstract: Background: The temporal cell surface expression of lymphocyte activated gene 3 (LAG3) on recently activated T cells presents an opportunity for targeted therapy in certain inflammatory diseases. LAG3 + cells are enriched in inflamed lesions in ulcerative colitis, 1 Crohn's disease and psoriasis. GSK2831781 is a highly potent, humanised IgG1, antibody-dependent cellular cytotoxicity-enhanced monoclonal antibody that depletes LAG3 + cells. Methods: A single escalating intravenous dose of GSK2831781 or placebo was administered to 40 healthy volunteers (up to 0.15 mg/kg). Three cohorts of nine patients with mild–moderate psoriasis were randomised to GSK2831781 (0.5, 1.5, or 5 mg/kg) or placebo in a 2:1 ratio. Safety, tolerability, pharmacokinetics (PK), and immunogenicity were evaluated. Circulating LAG3 + T cells were quantified using flow cytometry. LAG3 + and CD3 + cell counts and transcriptomics were assessed in psoriatic skin biopsies acquired prior to dosing and at Day 29. Psoriasis activity severity indices (PASI) and plaque lesion severity scores (PLSS) were profiled. Results: GSK2831781 was well-tolerated with no safety concerns identified. PK was non-linear, partly explained by target-mediated drug disposition; the non-linear process was saturated at doses ≥0.5 mg/kg. Dose-dependent depletion of circulating LAG3 + memory T cells was observed for 6–8 weeks following a single 5 mg/kg dose. LAG3 + and CD3 + (Figure 1) cells were reduced in psoriasis skin biopsies at 1.5 and 5 mg/kg. Preliminary analysis showed down-regulation of pro-inflammatory mRNA transcripts ( IL-17F, IFN-γ, and S100A12 ) and up-regulation of those associated with epithelial integrity ( CDHR1 ) which met the threshold of ≥1.5-fold change in median values vs. placebo at 5 mg/kg. There was no apparent decrease to Treg-associated transcripts ( IL-10 and FOXP3 ). GSK2831781 improved PASI and PLSS (Figure 1) at all doses (difference of estimated mean change from baseline in PLSS vs. placebo for 5 mg/kg, on Day 29 was −2.01 [95% CI: −3.57, −0.44]). The per cent change from baseline PLSS mean for 5 mg/kg, Day 29 was −30.9% (SD: 13.41) vs. placebo −1.9% (SD: 22.40). Conclusions: GSK2831781 effected dose-dependent depletion of LAG3 + T cells in blood, reduced LAG3 + and CD3 + cells in psoriatic skin and exhibited encouraging effects on pro-inflammatory and epithelial integrity transcripts, which translated into clinical improvements. These data are supportive of Phase II studies in other T-cell-related diseases, including inflammatory bowel disease. Reference 1. Slevin S, Tan M, Lahiff C, et al. Intestinal expression of LAG-3 correlates with inflammatory activity and response to biological therapy in ulcerative colitis. J Crohn's Colitis 2018;S125. doi:10.1093/ecco-jcc/jjx180.191